Nikaia’dan Yeni Yazıtlar VII Traianus’un Onurlandırılması - (:unkn) unknown (My University, 2017)
Antik dönemde Nikaia Kenti egemenlik alanında yer alan Sakarya İli’nin güneyi, dağların ve ovaların egemen yer şekillerini oluşturduğu Bithynia Bölgesi’nin güneyinde bulunmaktadır. Bu bölge arkeolojik ve epigrafik po¬tan¬siyelinden dolayı, XIX. yüzyılın ortalarından itibaren gezgin ve araş¬tır¬macıların hayli ilgisini çekmiştir: Nitekim C. Texier, F. K. Dörner, A. M. Schneider, S. Şahin ve Th. Corsten gibi araştırmacıların yörede epigrafya ve tarihî coğrafya ağırlıklı araştırmalar ve yayınlar yaptıkları görül-mektedir. Fakat tüm bu araştırma ve yayınlara karşın yörenin epigrafya, tarihî coğrafya ve iskân tarihi açısından yeniden değerlendiril-mesinin gerekliliği göz önünde tutularak; bölgede Epigrafik-Tarihi Coğrafi Yüzey Araştırması Projesi başlıklı bir çalışma yürürlüğe konulmuştur. Bu makalede 2010 yılın-da Nikaia egemenlik alanında bulunan Traianus için bir onurlandırma yazıtı tanıtılmaktadır.

Bithynia Region attracted the attention of the travellers and researchers since the mid-XIX. century due to the rich archaeological and epigraphic potential. It is seen that the researchers such as C. Texier, F. K. Dörner, A. M. Schneider, S. Şahin and Th. Corsten had conducted epigraphic and histori-cal geographical researches in Bithynia Region and made publications within this context. In spite of these researches and publications, by consideration that the region was not appropriately examined with regards to the epigraphy, historical geography and settlement history, a study under the title “Epigraphic Historical Geographical Surface Research Project Nicaea” was started in 2010 with the permission of the Ministry of Culture and Tourism in order to make up for the mentioned deficiency. In this article, the new honorific inscriptions for Traian found within the territory of Nicaea, during survey work undertaken in 2010, are presented.
NEW INSCRIPTIONS FROM NIKAIA VII A NEW HONORIFIC INSCRIPTION FOR TRAIAN
Keywords: Coğrafya